2015
DOI: 10.3390/w7031246
|View full text |Cite
|
Sign up to set email alerts
|

Robust Parameter Estimation Framework of a Rainfall-Runoff Model Using Pareto Optimum and Minimax Regret Approach

Abstract: This study developed a robust parameter set (ROPS) selection framework for a rainfall-runoff model that considers multi-events using the Pareto optimum and minimax regret approach (MRA). The calibrated parameter sets based on the Nash-Sutcliffe coefficient (NSE) for two events were derived using a genetic algorithm. We generated 41 combinations for weighting values between two events for the multi-event objective function and derived 41 Pareto optimum points that were considered as the ROPS candidates. Then, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
5
1
Order By: Relevance
“…This is equivalent to only consider NS in our research: using Zone 3 parameters to analyse uncertainty. However, the results in our study show the trade‐offs between robustness and NS , which cannot be revealed when robustness is not considered as in Kim et al ().…”
Section: Resultscontrasting
confidence: 89%
See 3 more Smart Citations
“…This is equivalent to only consider NS in our research: using Zone 3 parameters to analyse uncertainty. However, the results in our study show the trade‐offs between robustness and NS , which cannot be revealed when robustness is not considered as in Kim et al ().…”
Section: Resultscontrasting
confidence: 89%
“…In the research by Kim et al (), robustness is not considered as a criterion to select model parameters to analyse hydrological simulation uncertainty. This is equivalent to only consider NS in our research: using Zone 3 parameters to analyse uncertainty.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, many efforts have been made to identify, measure and reduce the uncertainty of parameters in CRR models. For example, in many studies multi-objective approach is deployed to reduce uncertainty in the parameter estimation [12][13][14], in some papers attempts have also been made to estimate the uncertainty parameter using methods such as the Generalize Likelihood Uncertainty Estimation (GLUE) and Sequential Uncertainty Fitting Procedure (SUFI) [15][16][17][18][19]. Furthermore, in several other studies, hybridization methods by combining hydrologic predictions from multiple competing models are applied to overcome the model structural uncertainty [20][21][22].…”
Section: Introductionmentioning
confidence: 99%